Faktor-faktor yang mempengaruhi ketahanan pangan rumah tangga di Kota Medan - Sihite, Nathasa Weisdania; Tanziha, Ikeu (AcTion: Aceh Nutrition Journal, 2021)
Sufficient food availability in an area does not guarantee household food security. Household food security is a condition for the fulfillment of food for every household both in terms of quantity and quality. The purpose of this research was to determine the factors related to household food security in Medan City.Â  The research design used was a cross-sectional design. The location was in Medan Kota and Medan Denai District that chosen purposively with criteria for poverty level is 15-20 percent. The household sample was taken randomly as 120 households with the criteria prosperity (Pra KS and KS 1,2,3). The result of the research shows that 67,5% of households were household food insecurity, and 32,5% of households were household food security. Household expenditure has a relationship with household food security (p= 0,000), while the age of the household head, number of family members, and education level did not show any relationship (p> 0,05). In conclusion, that household expenditure has a direct effect on the status of household food security in Medan City. There needs to be a strategy and active participation from the local government in overcoming the problem of household food security in Medan City.